2019
DOI: 10.11648/j.ajtab.20190504.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Capital Expenditures on Corporate Social Responsibility of Oil and Gas Firms in Nigeria

Abstract: This study is to ascertain the effect of human capital expenditures on corporate social responsibility of oil and gas firms in Nigeria It spanned for the period of 10 years (2008-2017) and made use of secondary data extracted from the financial reports and accounts of the oil and gas firms selected for the period. The study adopted ex-post facto research design and employed the panel least squares multiple regression analysis. Findings of the study provided empirical evidence that human capital expenditures pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Naji et al (2020),Abdullahi et al (2018), Rukumba (2021) and Ubesie, Eneh & Udeh[28], also found a strong and positive relationship between training and profitability. However,Suleiman et al (2018), had a contrary position in related research[25,27].…”
mentioning
confidence: 90%
“…Naji et al (2020),Abdullahi et al (2018), Rukumba (2021) and Ubesie, Eneh & Udeh[28], also found a strong and positive relationship between training and profitability. However,Suleiman et al (2018), had a contrary position in related research[25,27].…”
mentioning
confidence: 90%